1973
DOI: 10.1017/s0022112073000844
|View full text |Cite
|
Sign up to set email alerts
|

A visual study of turbulent shear flow

Abstract: The outer region of a turbulent boundary layer along a flat plate was photographed and analysed; in addition, limited observations of the wall area were also made. The technique involved suspending very small solid particles in water and photographing their motion with a high-speed camera moving with the flow.The single most important event observed in the outer region was fluid motion which in the convected view of the travelling camera appeared as a transverse vortex. This was a large-scale motion transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

1975
1975
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(29 citation statements)
references
References 3 publications
2
23
0
3
Order By: Relevance
“…While there was no indication that the detection was independent of either this level or the filter cutoff, ensemble averages depended only weakly on these settings.2 The detection scheme essentially focuses on the back of the structure where Brown & Thomas observed a "sharp" Blackwelder (1978) and sug gested that this front may be associated with an internal shear layer between accelerated and decelerated fluid regions (e.g. Nychas et al 1973).…”
Section: Conditional Sampling and Averaging Of Coherent Structuresmentioning
confidence: 99%
“…While there was no indication that the detection was independent of either this level or the filter cutoff, ensemble averages depended only weakly on these settings.2 The detection scheme essentially focuses on the back of the structure where Brown & Thomas observed a "sharp" Blackwelder (1978) and sug gested that this front may be associated with an internal shear layer between accelerated and decelerated fluid regions (e.g. Nychas et al 1973).…”
Section: Conditional Sampling and Averaging Of Coherent Structuresmentioning
confidence: 99%
“…Most of the experimental data, visual as well as other types, have been obtained at relatively low Reynolds numbers (in the range 1,000 < Re8 < 5,000 approximately) and any conclusions should be viewed with some caution. Furthermore, most of the observations are spatially limited: Visual observations usually cover a cross-sectional surface (Corino & Brodkey 1969, Grass 1971, Nychas et al 1973, Offen & Kline 1974, while velocity measurements at best give simultaneous data along a linear dimension, possibly including one additional spatial point (Blackwelder & Kaplan 1972). There is, in fact, insufficient information available to form a reliable kinematic picture of the flow.…”
Section: The Boundary Layermentioning
confidence: 99%
“…It has been shown that the smooth-wall region is characterized by a randomly recurring 'burst cycle' in which low-speed fluid near the wall is ejected violently into the overlying flow, immediately followed in time by a downsweep of higherspeed fluid into the region close to the wall (e.g., Kim et al, 1971;Nychas et al, 1973); also, intense, intermittent Reynolds-stress contributions and turbulent production rates are associated with these 'ejection' (or 'burst') and 'sweep' events (e.g., Wallace et al, 1972;Lu and Willmarth, 1973). For rough surfaces, there are only a few published studies (e.g.…”
Section: Introductionmentioning
confidence: 99%